2016
DOI: 10.1212/cpj.0000000000000268
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utility of seropositive voltage-gated potassium channel–complex antibody

Abstract: Background: Antibodies against voltage-gated potassium channel (VGKC)-complex are implicated in the pathogenesis of acquired neuromyotonia, limbic encephalitis, faciobrachial dystonic seizure, and Morvan syndrome. Outside these entities, the clinical value of VGKC-complex antibodies remains unclear. Methods: We conducted a single-center review of patients positive for VGKC-complex antibodies over an 8-year period. Results: Among 114 patients positive for VGKC-complex antibody, 11 (9.6%) carrying the diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…These antibodies may or may not be relevant to the patient's presentation depending on the clinical picture, and their presence should not preclude thorough exclusion of other potential causes of the neurological presentation. [31][32][33] The antibody level (for some antibodies like GAD65antibody), clinical presentation, disease course, CSF findings and smoking or cancer history are factors that can be used to determine the clinical relevance of the positive antibody. [33][34][35] The NAAs confidence scale is one suggested tool to increase the confidence in the clinical relevance of these less specific antibodies (table 3).…”
Section: Interpretation Of Naa Panel Resultsmentioning
confidence: 99%
“…These antibodies may or may not be relevant to the patient's presentation depending on the clinical picture, and their presence should not preclude thorough exclusion of other potential causes of the neurological presentation. [31][32][33] The antibody level (for some antibodies like GAD65antibody), clinical presentation, disease course, CSF findings and smoking or cancer history are factors that can be used to determine the clinical relevance of the positive antibody. [33][34][35] The NAAs confidence scale is one suggested tool to increase the confidence in the clinical relevance of these less specific antibodies (table 3).…”
Section: Interpretation Of Naa Panel Resultsmentioning
confidence: 99%
“…Retrospective review of low-positive VGKC cohorts has found that most cases were not associated with any encephalitic syndrome and those that were, had early prominent neurological symptoms (Hacohen et al, 2013;Huda et al, 2015;Jammoul et al, 2016;Paterson et al, 2014). Rather than being directly pathogenic, it is hypothesised that the antibodies in the low-positive VGKC cases may result from neuronal damage, such as in association with multiple sclerosis, amyotrophic lateral sclerosis or Creutzfeldt-Jakob disease, or may indicate non-neuronal autoimmunity (Fujita et al, 2012;Huda et al, 2015;Jammoul et al, 2016;Lang et al, 2017). In addition, VGKC antibodies may be an oncogenic marker, with higher than expected rates of malignancy seen, even in low-positive cases scanning (Jammoul et al, 2016;Klein et al, 2013;Paterson et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Rather than being directly pathogenic, it is hypothesised that the antibodies in the low-positive VGKC cases may result from neuronal damage, such as in association with multiple sclerosis, amyotrophic lateral sclerosis or Creutzfeldt-Jakob disease, or may indicate non-neuronal autoimmunity (Fujita et al, 2012;Huda et al, 2015;Jammoul et al, 2016;Lang et al, 2017). In addition, VGKC antibodies may be an oncogenic marker, with higher than expected rates of malignancy seen, even in low-positive cases scanning (Jammoul et al, 2016;Klein et al, 2013;Paterson et al, 2014). No low-positive VGKC case in this study had evidence of neurological illness or malignancy, although this cohort is significantly younger than other neurological VGKC cohorts described, but two cases did have a past history of non-neurological autoimmunity (Pozo-Rosich et al, 2003;Tan et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations